35 GENE EXPRESSION ANALYSIS OF EUROPEAN-AMERICAN LUPUS PATIENTS WITH THYROID DISEASE COMPARED TO MATCHED CONTROLS. (1st January 2005) - Guo, L.; Dominguez, N.; Dozmorov, I.; Tang, Y. H.; Namjou, B.; Kelly, J.; Hutchings, D.; Bruner, G.; Klein, W.; James, J.; Kaufman, K.; Scofield, H.; et al.
Abstract : Purpose: We have studied gene expression in Epstein-Barr virus transformed B cell lines to define differences between SLE patients and matched controls. We used this design to remove, to the extent possible, environmental influences and the secondary changes in gene expression caused by lupus and found in peripheral blood cells from patients who are ill. In the present study, we have focused on gene expression analysis of cell lines derived from European-American lupus patients who also present evidence of thyroid disease compared to unrelated matched controls. Methods: 12 European-American SLE patients were selected according to American College of Rheumatology (ACR) criteria for SLE and their contribution to the 5q14 (lupus affected with autoimmune thyroid disease) genetic linkage. 12 controls were matched by age, sex, race, and state of residence. Human genome U133 plus 2.0 arrays (Affymetrix) were used for each subject. Gene expression differences were evaluated for genes with p < .05 for the paired t-test, p < .0001 for the associative t-test, and an apparent ratio of expression of > 2.0 or < 0.5. Results: The affecteds from pedigrees linked at 5q14 differently expressed 191 genes when compared to controls (59 up-regulated, 54 down-regulated, 19 only in lupus patients, and 59 only in matched controls). Two of the differentially expressed genes were located in 5q14 intervals. The differentially expressed genes include members of signal transduction pathways, thyroid hormone receptor, small nuclear ribonucleotide proteins and immune response related genes. Conclusions: We identified genes by differential gene expression analysis of cell lines derived from European-American lupus patients with thyroid disease. Two of these genes come from within the genetic linkage interval identified in other studies of this subset of lupus patients.